Something Called the ‘False Dilemma Fallacy’ (FDF): A Return to Formalization Just This Time - Conces, Rory J.; Walters, Matthias (Informal Logic, 2023)
This work is a revision of the False Dilemma Fallacy (FDF). The formalized model (FM)of this fallacy has as its centerpiece a valid disjunctive syllogism, but the disjunctive premise is presumed to be false, thus making the argument unsound. Our revised model (FM2.0) focuses on the formal structure by comparing the given vs. the real argument, which is unsound because of its invalidity. This approach we believe is more pedagogically useful and a better explanation of the fallacious nature of the FDF. It extends the identity of “formal fallacy” to the FDF. The abstract is formatted in two columns. The English abstract goes on this side.